THE EFFECT OF ORGANIZATIONAL CULTURE AND SPIRIT AT WORK ON THE PERFORMANCE OF INDONESIAN FARMER COOPERATIVE (KPI) EMPLOYEES IN MEDAN CITY - Putri Balqis; Onan Marakali Siregar (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2022)
Cooperatives are a place for a group of people to cooperate to improve the economic welfare together. Cooperatives have professionally managed human resources who can help balance the Indonesian economy and the growth of the cooperative's sales targets. The Indonesian Farmers Cooperative (KPI) in Medan City, which has not yet maximized the performance produced by the members of the cooperative which resulted in a decrease in sales produced by the cooperative. The researcher discusses the Influence of Organizational Culture and Spirit at Work on Employee Performance of the Indonesian Peasants Cooperative (KPI) in Medan City. The form of research used in this research is quantitative by using the associative approach method. The results of this study indicate that the variables of organizational culture and work spirit together affect employee performance variables. It can be seen in the results of the Simultaneous test (F test) which shows that the Fstatistic value obtained is 49.966, which means that the fstatistic value is greater than the Ftable value, namely 49.966 > 3.32 or based on a significant value that is 0.000 <0.05. Determination test shows that R is 0.877 or 87.7%, the remaining 24.6% is influenced by other variables that are not explained in this study. In conclusion, the organizational culture variable (X1) and the work spirit variable (X2) have a positive and significant effect on employee performance.